In situ synthesis of bacterial cellulose/polycaprolactone blends for hot pressing nanocomposite films production - Figueiredo, Ana R. P.
A series of bacterial cellulose (BC)/polycaprolactone (PCL) nanocomposite films were successfully prepared by supplementation of the BC culture medium with variable amounts of PCL powder followed by hot-pressing of the BC/PCL mixtures obtained after incubation. PCL powder was fully incorporated into the BC network during its production and did not change the BC network morphology. The obtained films showed a homogenous distribution of PCL throughout the BC network, as well as good thermal stability (up to 200 degrees C) and improved mechanical properties, when compared to pristine PCL. In addition, the intrinsic biodegradability and biocompatibility of the nanocellulose fibers and PCL opens the possibility of using this novel nanocomposite in the biomedical field and food packaging. The BC biosynthetic approach combined with the hot-pressing proved successful for the sustainable development of nanocomposites combining hydrophobic thermoplastic matrices and hydrophilic nanocellulose fibers, without the use of harmful organic solvents commonly used to dissolve this type of polymeric matrices. (C) 2015 Elsevier Ltd. All rights reserved.